2015
DOI: 10.1097/bsd.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of the Pedicle Screw Insertion Depth Effect on Screw Stability Under Cyclic Loading and Subsequent Pullout

Abstract: Although increased screw depth led to increased fixation and decreased loosening, additional purchase of the stiff anterior cortex is essential to reach superior screw-bone construct stability and stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 44 publications
0
55
1
4
Order By: Relevance
“…Therefore, radial stress resistance may be more important than axial pullout strength in preventing the screw from loosening, which contradicts the standard axial pullout test established by the ASTM in publications F543 and F1717 . Furthermore, the effectiveness of the pullout test in predicting the pedicle screw loosening is controversial as it does not simulate physiological loading conditions; therefore, screws with a higher axial pullout strength do not necessarily possess a lower loosening rate. The study confirmed that standard axial pullout testing could not conclusively assess the screws’ stability when used in long bone fracture plate fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, radial stress resistance may be more important than axial pullout strength in preventing the screw from loosening, which contradicts the standard axial pullout test established by the ASTM in publications F543 and F1717 . Furthermore, the effectiveness of the pullout test in predicting the pedicle screw loosening is controversial as it does not simulate physiological loading conditions; therefore, screws with a higher axial pullout strength do not necessarily possess a lower loosening rate. The study confirmed that standard axial pullout testing could not conclusively assess the screws’ stability when used in long bone fracture plate fixation.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the pedicle screw found that pullout strength was an unsuitable predictor of pedicle screw loosening as it does not simulate physiological loading conditions . The toggling test, which can simulate physiological loading conditions, is a better predictor than the axial pullout test . Therefore, radial stress resistance may be more important than axial pullout strength in preventing screw loosening.…”
mentioning
confidence: 99%
“…Another contributing factor to some cases of spinal hardware fixation failure is the implant site. In patients with osteoporosis, the low-density bone of the spine increases the risk for implant loosening or pullout (Karami et al, 2015). In response to implant loosening, screw augmentation with various fixatives such as hydroxyapatite, polymethylmethacrylate, or tricalcium phosphate have been employed as potential solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Caudo-cephalad loading in an in vitro setting (10) is well established and can be used as a preconditioning step prior to pullout or can itself be an endpoint for loosening (41)(42)(43)(44)(45)(46). Toggling generally decreases the stability of the screw/bone construct (11,32), however, this is not always the case. Lotz et al (47) reported pullout loads of 809±467 N without cyclic loading and 801±265 N following cyclic loading.…”
Section: Comparison To Existing Literaturementioning
confidence: 92%
“…Screw pull-out studies using human cadaveric tissues report a wide range of values from 102 to 1,741 N (15,26,28,(31)(32)(33)(34). Similarly, screw pull-out with the calf model reports values from 747 to 7,300 N, depending on treatment (30,35).…”
Section: Comparison To Existing Literaturementioning
confidence: 99%